2000
DOI: 10.1097/00005537-200009000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Complications in Children After Bone Marrow Transplantation

Abstract: (30%) were difficult. These difficult intubations occurred in 16 (30%) patients. Patients with Hurler syndrome and congenital immunodeficiencies had significantly more difficult intubations than children with leukemia. The incidence of complications causing difficult intubation were difficulty visualizing cords, because of the presence of blood (63%); difficulty visualizing cords, because of edema (19%); anatomically narrowed airway (13%); limited neck extension (13%); and limited jaw opening (6%). The resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…As a practical point, we would like to highlight the difficulty in intubation in MPS-IH because of abnormal anatomy. 8 It is even more difficult when there is diffuse PH with blood obstructing the view of the vocal cords. Moreover, PH has a tendency to reoccur as for patients 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…As a practical point, we would like to highlight the difficulty in intubation in MPS-IH because of abnormal anatomy. 8 It is even more difficult when there is diffuse PH with blood obstructing the view of the vocal cords. Moreover, PH has a tendency to reoccur as for patients 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…Drew et al 30 reported on the associated airway complications in 832 pediatric BMTs performed over a 4-year period. Of the 832 patients, 87 (10.5%) required mechanical ventilation, with difficult intubations in 16 patients (30%).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…A key organ affected by complications of HSCT is the lung, with potential development of infectious pneumonia, idiopathic pneumonitis, bronchiolitis obliterans with organizing pneumonia, bronchiolitis obliterans, pulmonary hemorrhage, and pulmonary edema [16][17][18][19][20]. Ultimately, about 11% to 29% of children undergoing HSCT will require admission to an intensive care unit for respiratory support [21][22][23][24][25][26][27][28][29].…”
mentioning
confidence: 99%